Short-term effects of estradiol and bisphenol A on gene expression associated with early head mineralization in the seabass Dicentrarchus labrax - Farcy, Emilie; Potier, Eric; Leurs, Nicolas; Gasset, Eric; Dutto, Gilbert; Lallement, Stéphane; Bourdy, Clarence; Debiais-Thibaud, Mélanie; Martinand-Mari, Camille (Frontiers in Marine Science, 2022)
Introduction Natural and synthetic estrogens are pollutants found in aquatic ecosystems at low concentrations reaching ng.L-1 to μg.L-1. At these concentrations, they are able to interfere with the fish endocrine system. When waterborne exposure occurs at early life stages, when blood estrogens concentrations are low, this may have significant consequences for estrogen-sensitive functions such as skeletal development. Methods To better understand how (xeno)estrogens may affect early head mineralization, 12 days post-hatch larvae of the European seabass Dicentrarchus labrax were experimentally exposed for 4 days to the natural estrogen estradiol E2 and to the xenoestrogen bisphenol A (BPA), both used at either regulatory concentration of water quality or a 100 times higher concentration. Head mineralization level was assessed using Alizarin red staining, together with the relative quantification of mRNA expression levels of several genes playing key roles in skeletogenesis and estrogen signaling pathways. Results We showed that (xeno)estrogen exposure at early larval stage increases the expression of skeleton-associated genes: matrix proteins encoding genes (col1a2, col2a1a, col2a1b, bgp1a, bgp1b, sparc), proteolytic enzyme encoding genes (ctsk) and transcription and signaling factors (sox9a, sox9b, ihha, runx2, rankl). Although transcriptional overexpression of these genes was significant in larvae exposed to 40 ng.L-1 E2 and to 1.6 and 160 μg.L-1 BPA, increased mineralization was detected only in E2-exposed larvae, suggesting a difference in head skeleton development and remodeling in BPA-treated larvae. Discussion Our results suggest that these phenotypic differences could be due to the implication of other estrogenic signaling pathways involving both nuclear and membrane-bound estrogen receptors (ERs and GPERs), but also estrogen-related receptors (ERRs). This study brings new insights into the regulatory mechanisms of skeletogenesis by E2 and BPA and into the effects of waterborne exposure to (xeno)estrogens on the early skeletal development of teleost fishes.